Tourist's Bizarre Behaviors in Bali: Deconstruction of Irritation Index Theory from Gen Z Perspective - Prabawa, I Wayan Sukma Winarya; Suwintari, I Gusti Ayu Eka; Semara, I Made Trisna; Effendie, Mahardhika Wijaya; Pertiwi, Putu Ratih (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2025)
The urgency of this research arises from the diminishing reputation of Bali tourism, attributed to the viral dissemination of peculiar tourist behaviors via social media and other platforms. If this persists, it may adversely affect Bali's tourism circumstances. The research aims were: 1) to detect and analyze alterations in individuals' attitudes resulting from exposure to negative tourism information, and 2) to develop a model linking negative tourism information exposure to changes in the attitudes of the Balinese people, with the fatigue component serving as a mediating variable. This study employed a quantitative methodology, utilizing data analysis approaches that included quantitative descriptive analysis and Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The study's findings indicate that 1) the populace remains in the "euphoria" phase, characterized by a continued acceptance of tourists, and 2) the variable of fatigue effectively mediates the impact of negative tourism information on public attitudes, exhibiting partial mediation